To read listening: Reflections on audiobooks as an emerging sector - Cordón-García, José-Antonio (Anuario ThinkEPI, 2018)
The electronic publishing sector has experienced a slowdown over the past two years; however, one segment has grown. The audiobook has seen extraordinary growth in all advanced countries. It is not a new genre, since it dates back to the beginning of the 20th century, but audiobook producers have exploited the audiobook´s maximum possibilities by optimizing the benefits for very diverse contexts, for all kinds of daily activities. Research into audiobooks raises some important points for discussion that are analyzed in this article, such as the relationship between comprehension and hearing, the differences between auditory and print environments, quality control systems in relation to their presentation, and dissemination systems. An analysis of these points also includes the read-listen dilemma as measurement parameters from the point of view of the consideration of this new genre as a part of the reading concept.
Keywords: Audiobooks; Reading comprehension; E-books; Digital reading.